Full Online Teacher Training Service Scheme on Improving Pedagogical and Professional Competencies - Arifmiboy Arifmiboy; Iltavia Iltavia; Iswandi Iswandi (Nidhomul Haq : Jurnal Manajemen Pendidikan Islam, 2024)
Implementing teacher teaching training services for Islamic Religious Education and Islamic School teachers in the Indonesian Ministry of Religious Affairs ranks in 2021 was carried out with a complete online scheme. Implementing in-service teaching training aims to produce professional educators with academic, professional, personal, and social competencies. The difference in participants' conditions, such as different areas, technology tools mastery, and infrastructure availability, became a challenge for LPTK organizers. The article aims to measure the effectiveness of implementing teacher teaching training services in a whole online scheme at LPTK of the State Islamic University of Bukittinggi in 2023. This evaluation research was conducted in LPTK of the State Islamic University of Bukittinggi in 2023. The sample was selected by purposive technique with the number of samples 416 teachers, consisting of 266 Islamic Religious Education teachers and 150 Islamic School teachers. The data was collected by distributing questionnaires and analyzed using descriptive statistics. The results showed that the average paedagogic and professional competencies achievement score was 86.90 points, with a high interpretation of achievements. The implementation of teacher teaching training service in an entire online scheme at LPTK of the State Islamic University of Bukittinggi in 2023 has increased effectiveness.